Swiss family physicians and home visits: a 10-year retrospective analysis and typology based on billing data (Swiss Medical Weekly, 2021)
INTRODUCTION In the context of an aging population, homecare visits by family physicians may contribute to maintaining older patients at home; however, home visits by family physicians have decreased in number in the last decade with the emergence of homecare-oriented healthcare services. We aimed to describe the diversity of activities and evolution over time of home visits by Swiss family physicians. METHODS This was a retrospective observational descriptive study. We used billing data collected by the cantonal trust centre for home visits made by family physicians of the canton of Vaud, Switzerland from 2006 to 2015. We separated billed items into specific categories, including the Tarmed catalogue (Swiss pricing system for medical services), laboratory catalogue, medications, medical material and vaccines. We compared billing patterns between emergency and routine visits. We used discrete mixture models to identify cluster classes of visits, and compare their characteristics. RESULTS From 2006 to 2015, Vaud family physicians made 451,634 home visits for which they billed a median of 5 items per visit (range 2–95). Most home visits (65%, 293,713) were routine visits consisting of consultation time without additional investigation. We identified four cluster classes of visits comprising routine visits, routine visits with laboratory tests, emergency visits during the day and emergency visits during the night. Routine visits were the main cluster class while emergency home visits were rare. CONCLUSIONS Family physician home visits are mainly routine visits without additional investigation. Thus, we wonder if a part of this activity could be delegated to other healthcare professionals.